Cascalho de perfuração de poços de petróleo e gás. Estudo do potencial de aplicação em concreto - Fialho, Poline Fernandes (2012)
The drilling of petroleum wells generates many residues such as waste fluids and drill cuttings. The management of those drilling wastes has been a problem to the petroleum and gas industry not only due to the significant amount of residues generated but also due to the presence of both organic and inorganic contaminants in their composition. Studies for the reuse of drill cuttings in building materials are recent. They show possible alternatives of use of this material such as in pavement sub-base layers, in ceramic materials, and in cement-based materials. This research aimed to evaluate the behavior of two types of drill cuttings as a replacement and as an addition in unarmed concrete. Laboratory tests were performed to characterize the materials used in the concrete fabrication, in particular the drill cuttings, as well as control testing in concrete technology. The obtained results in this research showed that the interactions of drill cuttings with cement-based materials are related to their previous characterization. The replacement of sand by drill cuttings from the first phase of well drilling in the concrete mixture significantly changes the rheology of fresh concrete. The proportions tested did not compromise the concrete mechanical properties. Changes in concrete microstructure were only observed in the concrete samples with the addition of drill cuttings from the third phase of well drilling process. Those have become more porous and the formation of hydrated compounds occurred more slowly. The method of qualitative detection of free chloride did not identify chlorides in the concrete samples. Finally, it can be concluded that it is possible either the replacement of drill cuttings in concrete considering the levels tested in this study.